Effect of D-Alpha Tocopherol Therapy towards Malondialdehyde Level and Histology of Kidney in Rattus norvegicus with MLD-STZ Induction - Marissa Agnestiansyah Mahardhian; Aulanni’am Aulanni'am; Chanif Mahdi (Chemistry Department, The University of Brawijaya, 2013)
Diabetic Nephropathy is a kidney disease which occurs due to complication of diabetes mellitus as a consequence of the damage of the kidney endothelial cells. Hyperglicemia condition in patients with diabetes mellitus that induces an oxidative stress, were related to endothelial cell damage. Oxidative stress as a result of hyperglycemia will activate a number of signal transduction pathways resulting in increase of free radicals. D-alpha tocopherol as one of antioxidant substance, that can act as an inhibitor of free radical chain reactions, play an important role in the reduction of the oxidative stress effect. Effect of D-alpha-tocopherol in reducing oxidative stress is identified by the levels of malondialdehyde (MDA) in kidney and histology of kidney. This study used five groups mice; they were a control group, a diabetic group which was induced with MLD-STZ, and a therapeutic groups with a varieties doses of D-alpha tocopherol (100 mg/kgBW, 200 mg/kgBW and 300 mg/kgBW). The results showed that the D-alpha tocopherol was able to reduce the levels of malondialdehyde (MDA) and repair the histology of kidney of mice induced by MLD-STZ.